Palladium-Catalyzed Decarboxylative Benzylation of Acetylides and Enolates - Torregrosa, Robert R. P.; Mendis, Shehani N.; Davies, Alex; Tunge, Jon A. (Synthesis, 2018)
Benzylic alkylation of enolates and acetylides has been achieved through the use of a decarboxylative benzylation strategy. Previous research in this area is often limited by the need for extended conjugation in the electrophiles that are coupled. Herein, we report that the use of 1,1'-bis(diphenylphosphino)ferrocene (dppf) ligand allows the coupling of simple benzyl electrophiles with enolates, while the use of XPhos ligand promotes the decarboxylative couplings of propiolates.
Keywords: decarboxylative coupling; acetylide; enolate; benzylation; palladium